High-Quality Genome of the Medicinal Plant Strobilanthes cusia Provides Insights Into the Biosynthesis of Indole Alkaloids - Hu, Yongle; Ma, Dongna; Ning, Shuju; Ye, Qi; Zhao, Xuanxuan; Ding, Qiansu; Liang, Pingping; Cai, Guoqian; Ma, Xiaomao; Qin, Xia; Wei, Daozhi (Frontiers in Plant Science, 2021)
Strobilanthes cusia (Nees) Kuntze is an important plant used to process the traditional Chinese herbal medicines “Qingdai” and “Nanbanlangen.” The key active ingredients are indole alkaloids (IAs), which exert antibacterial, antiviral, and antitumor pharmacological activities and serve as natural dyes. We assembled the S. cusia genome at the chromosome level through combined PacBio circular consensus sequencing and Hi-C sequencing data. Hi-C data revealed a draft genome size of 913.74 Mb, with 904.18 Mb contigs anchored into 16 pseudo-chromosomes. Contig N50 and scaffold N50 were 35.59 and 68.44 Mb, respectively. Of the 32,974 predicted protein-coding genes, 96.52% were functionally annotated in public databases. We predicted 675.66 Mb repetitive sequences, 47.08% of which were long terminal repeat retrotransposons. Moreover, 983 Strobilanthes-specific genes (SSGs) were identified for the first time, accounting for approximately 2.98% of all protein-coding genes. Further, 245 putative centromeric and 29 putative telomeric fragments were identified. Transcriptome analysis identified 2,975 differentially expressed genes (DEGs) enriched in phenylpropanoid, flavonoid and triterpenoid biosynthesis. This systematic characterization of key enzyme-coding genes associated with the IA pathway and basic helix-loop-helix (bHLH) transcription factor family formed a network from the shikimate pathway to the indole alkaloid synthesis pathway in S. cusia. The high-quality S. cusia genome presented herein is an essential resource for traditional Chinese medicine genomics studies and understanding the genetic underpinning of IA biosynthesis.